A Discourse Analysis of TEDx Talks Video Entitled “Break The Ceiling Glass” By Prilly Latuconsina - Denti Zentia Putri; Safnil Arsyad (UNIB Press, 2023)
Women have always been associated with societal standards. The current societal standards are considered by society not to make quality women because they are only fixated on the assumption that women are creatures who always depend on other people. Like a new article entity that leads